2022
DOI: 10.1200/jco.21.02844
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Year Benefit From Adjuvant Goserelin and Tamoxifen in Premenopausal Patients With Breast Cancer in a Controlled Randomized Clinical Trial

Abstract: PURPOSE To assess the long-term (20-year) endocrine therapy benefit in premenopausal patients with breast cancer. METHODS Secondary analysis of the Stockholm trial (STO-5, 1990-1997) randomly assigning 924 premenopausal patients to 2 years of goserelin (3.6 mg subcutaneously once every 28 days), tamoxifen (40 mg orally once daily), combined goserelin and tamoxifen, or no adjuvant endocrine therapy (control) is performed. Random assignment was stratified by lymph node status; lymph node–positive patients (n = 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…A recent study by the first and last authors 10 of the present study suggested that a little more than 4 min/d of VILPA is also associated with a reduction in risk of cardiovascular disease, cancer, and all-cause mortality in both exercisers and nonexercisers. 10 Lifestyle and habits of physical activity have been shown to be mostly stable over time; however, there is a need for large and extended longitudinal studies to give a more complete understanding and the possibility for exploring the importance of other factors associated with physical activity. Rarely measured precisely (eg, with pedometers or microcomputer sensors), physical activity is most frequently quantified by responses to questionnaires.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…A recent study by the first and last authors 10 of the present study suggested that a little more than 4 min/d of VILPA is also associated with a reduction in risk of cardiovascular disease, cancer, and all-cause mortality in both exercisers and nonexercisers. 10 Lifestyle and habits of physical activity have been shown to be mostly stable over time; however, there is a need for large and extended longitudinal studies to give a more complete understanding and the possibility for exploring the importance of other factors associated with physical activity. Rarely measured precisely (eg, with pedometers or microcomputer sensors), physical activity is most frequently quantified by responses to questionnaires.…”
supporting
confidence: 58%
“…For most diseases including cancer, different types of physical activity may possibly also give a differential risk decrease depending on the specific subtype of the disease. For instance, premenopausal and postmenopausal breast cancers with different biology and hormonal milieu may be influenced differently by physical exercise…”
mentioning
confidence: 99%
“…No adverse interaction between tamoxifen and goserelin was identified although this larger patient population was not selected for genomic risk. Nonetheless, findings of differential efficacy as demonstrated by Johansson et al, 2 if replicated in other data sets, would be extremely useful to try to tailor adjuvant endocrine therapy for premenopausal women in a more precise way than through reliance on traditional clinical markers such as stage and conventional biomarkers alone. A challenge for any validation is likely to be the availability of tissues for analysis from some of the older trials of OFS and selection of the best multigene test.…”
mentioning
confidence: 91%
“…In the article that accompanies this editorial, Johansson et al 2 report better distant recurrence free interval at 20 years in a randomized trial for premenopausal women with early‐stage estrogen receptor–positive breast cancer after only 2 years of tamoxifen, goserelin, or the combination when compared with placebo. The results confirm the long-term value of endocrine therapy for these young women and suggest that further work using multigene assays may help to tailor selection of endocrine therapy in this setting.…”
mentioning
confidence: 99%
“…This is of particular importance, since the sialylation pattern is known to be modulated by chemical and biological stimuli. Although the advances in immunotherapy and targeted therapy of breast cancer are in the focus of clinicians, selective oestrogen receptor modulators (SERMs) are the strategy of choice for the management of breast tumours in clinical practice [ 24 , 25 ]. Tamoxifen (TMX) is a non-steroid anti-oestrogen drug widely used in the therapy for and prevention of breast cancer in pre- and post-menopausal women [ 26 ].…”
Section: Introductionmentioning
confidence: 99%